Skin aging - the role of nutrition and sugar - Białoszycka, Żanna; Białoszycka , Monika; Pachevska , Alisa; Istoshyn , Valerij; Biloshytska , Alina (Journal of Education, Health and Sport, 2025)
Introduction. The skin is the largest organ of the human body, covering almost the entire surface. It performs numerous functions essential for life and normal functioning. Skin aging is a complex process involving both intrinsic and extrinsic changes. It can be classified into intrinsic and extrinsic aging. Among these, sun exposure is undoubtedly the most significant and primary exogenous factor, with its effects depending on intensity and duration. The accumulation of advanced glycation end products (AGEs) significantly affects skin aging. Aim of the study. This review aims to present and summarize the roles of key factors influencing skin aging, emphasizing the importance of healthy nutrition as a method to slow down the aging process. Materials and Methods. A literature review was conducted using the PubMed database to identify relevant studies from the past twenty years. The most significant findings were compiled in this review. The literature was selected using keywords such as "skin aging," "skin and effects of sugar," and "skin and glycation." Results. Among extrinsic factors, sun exposure is the most significant. Diets high in fats delay skin healing, promote oxidative stress, and induce inflammatory reactions in the skin. Excess dietary fats can also lead to morphological changes and impaired matrix remodeling in the skin. Among the mechanisms underpinning skin aging, glycation is one of the most extensively studied. Glycation is a non-enzymatic process where proteins, lipids, and nucleic acids covalently bind with sugar molecules, typically glucose or fructose. Conclusion. Various exogenous factors influence the skin’s condition, accelerating aging, contributing to skin diseases, and increasing carcinogenesis risk. Evidence supports the effectiveness of sunscreen use and limiting sun exposure to prevent skin aging. Furthermore, a balanced diet rich in antioxidants, with reduced free sugars and carbohydrates, can lower AGE production in the skin.